Building a Political Image Through Digital Space: Study of the Three Heads of the Gerindra, Golkar, and Democratic Party - Kharisma, Bella; Zaenuri, Muchammad (Universitas Muhammadiyah Yogyakarta, 2025)
Ahead of the 2024 elections, political parties have begun to prepare themselves in choosing their candidates. In fact, some political parties have decided to carry their general chairman to become President or vice president. The political parties are Democrats with their chairman Agus Harimurti Yudhoyono, Golkar with Airlangga Hartarto, and Gerindra with Prabowo Subianto. Therefore, this study aims to investigate the utilization of digital space by political party leaders in building electability for the 2024 Indonesian elections. The novelty of this research lies in its exploration of how digital platforms, specifically Twitter, shape the strategies of political leaders in Indonesia's contemporary electoral landscape, providing fresh insights into the evolving nature of political campaigning in the digital age. This study used a qualitative method and literature study data collection techniques. This study uses NVIVO 12 analysis software to analyze data. The findings in this study show that the three political party leaders used Twitter facilities to build their political electability for the 2024 elections as part of their efforts to become potential candidates. The intensity of use does not necessarily influence the utilization of digital space for political candidates to build political electability but also involves other factors, namely in the form of loyalist capital and the popularity of previous political experience. This is a reinforcement for political candidates to expand the electability of voters by targeting digital users. Therefore, this research will contribute to the further development of the theory of political electability, specifically in the context of the influence of social media usage, particularly Twitter, on increasing the electability of political party leaders. It aims to support and strengthen previous studies on similar issues related to enhancing the electability of political leaders ahead of the 2024 elections.